2013
DOI: 10.1177/1082013212442180
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing gamma-aminobutyric acid content in germinated brown rice by repeated treatment of soaking and incubation

Abstract: Gamma-aminobutyric acid (GABA), commonly produced by germination of brown rice grain, is a free amino acid which could help relieving or preventing non-communicable diseases in human. Several research works have been conducted on GABA production from germinated brown rice. However, the yielded GABA (10.1-69.2 mg/100 g germinated brown rice) was comparatively low; thus the amount was insufficient to be used as active ingredients in functional foods. The objective of this study was to explore alternative methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…were recorded to be higher than those detected in germinated brown rice (0.0818 ± 0.0072 g/100 g). This may be contributed by the different level of GABA-synthesizing enzyme that is present in different plants [23]. In this study, germinated mung bean extracts contained higher level of GABA as compared to fermented mung bean extracts.…”
Section: Discussionmentioning
confidence: 66%
“…were recorded to be higher than those detected in germinated brown rice (0.0818 ± 0.0072 g/100 g). This may be contributed by the different level of GABA-synthesizing enzyme that is present in different plants [23]. In this study, germinated mung bean extracts contained higher level of GABA as compared to fermented mung bean extracts.…”
Section: Discussionmentioning
confidence: 66%
“…The GABA concentration in barley and wheat is less than 2 mg/100 g of dm (Ohm et al, 2016), while in regular brown rice grains it ranges from 3 to 7 mg/100 g of dm (Banchuen, Thammarutwasik, Ooraikul, Wuttijumnong, & Sirivongpaisal, 2009;Charoenthaikij et al, 2010;Chen et al, 2016). It is present in higher concentrations in sprouted barley and wheat (7 to 25 mg/100 g) (H. Chung, Jang, Cho, & Lim, 2009;Ohm et al, 2016), and especially sprouted brown rice (35 to 80 mg/100 g of dm) (Banchuen et al, 2009;Chungcharoen et al, 2015;Cornejo et al, 2015;Ohm et al, 2016;Ohtsubo et al, 2005;Roohinejad et al, 2011;Thitinunsomboon, Keeratipibul, & Boonsiriwit, 2013). Charoenthaikij et al (2010), Cornejo et al (2015), and Roohinejad et al (2011) observed a 8-to 12-fold increase in GABA content in brown rice when sprouted for 2 to 4 days at 27 to 35°C.…”
Section: Impact Of Sprouting On γ -Aminobutyric Acid Content In Brownmentioning
confidence: 99%
“…The GABA content in sprouted brown rice increases up to 120 to 130 mg/100 g of dm when the kernels are steeped at 30°C in lactic or citric acid solutions (pH 3.0 to 5.6) prior to germination for 1 to 2 days at 30 to 35°C. Indeed, an acidic pH is more optimal for rice embryo glutamic acid decarboxylase action (Banchuen et al, 2009;Thitinunsomboon et al, 2013;Zhang et al, 2014). It is noteworthy that GABA is very heat-stable and that it is not degraded during kilning/drying (Chungcharoen et al, 2015;Ohtsubo et al, 2005).…”
Section: Impact Of Sprouting On γ -Aminobutyric Acid Content In Brownmentioning
confidence: 99%
“…6 GABA of brown rice can be stimulatory produced by germination. 4 In analysis of GABA content in germinated Sang-Yod rice, the level of 10 mg/100g rice was detected (unpublished data). This quantity conforms to the standard for GABA rice of Thailand (in Thai version, not cited).…”
Section: Resultsmentioning
confidence: 98%
“…18 Besides GABA, glutamate has been enormously supplied by germinated Sang-Yod rice. 4 It might be beneficial to people who aim to control their weight, to increase GABA concentration in their brain, and to improve learning ability and memory by consuming GABA-rich rice as daily carbohydrate source.…”
Section: Resultsmentioning
confidence: 99%